Analisis Faktor Loyalitas Konsumen Dan Kualitas Pelayanan Terhadap Minat Beli Pada Azzairi Mart Pakisan Tlogosari Bondowoso Perspektif Ekonomi Syariah - Rofiullah, Ahmad Hendra (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This research aims to analyze the factors of consumer loyalty and service quality on purchasing interest at Azzairi Mart. This type of research is quantitative research, research used to test the relationship or influence of variables using purposive sampling techniques, namely determining the sample with certain considerations. The samples taken in this study were all students of the Abu Zairi Salafiyah Islamic Islamic Boarding School, namely 230 respondents consisting of male and female students, but not all were used as samples, the selected sample was 150 respondents who used the Slovin formula.Based on the results of descriptive analysis, the frequency of consumer loyalty respondents' answers has an average index value of 123.5 with very high criteria. And the results of descriptive analysis of the frequency of respondents' answers to service quality have an average index value of 127.3 with very high criteria. And the results of the descriptive analysis of the frequency of respondents' answers to buying interest have an average index value of 123 with very high criteria. And from the results of the multiple linear regression test, the consumer loyalty variable does not have a significant effect on purchasing interest where the significant value is (0.089) > 0.05(a=5%) so the hypothesis is rejected. And the service quality variable has a significant effect on purchase intention, because the significance value is (0.000) < 0.05(a=5%) so the hypothesis is accepted.